Germ Cell Tumors in the Mediastinum - Sulthansyah, Muhammad Harris Sis; Lestari, Lilik (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background:  Germ mediastinum tumors grow in the mediastinum and consist of teratoma, seminoma, and nonseminomatous. Cases of germ mediastinum tumors are rare. During the last decade, only two cases have been found at Dr. Ario Wirawan Lung Hospital, Salatiga, Indonesia.Objective: Germ mediastinum tumor is a rare case. This paper aims to present a case report that would benefit the radiology database.Case Presentation: Two male patients aged 18 and 19 were referred to radiology complaining of continuous shortness of breath and coughing. The shortness of breath does not decrease daily, so the patient uses a breathing apparatus to help reduce shortness of breath. The patient underwent chest X-rays, ultrasonography (USG), and computerized tomography (CT). Pleural effusion is seen, the COR of the right heart border is good, the heart border is covered with a homogeneous covering, and the location of the heart is pushed to the right. The USG results showed a lot of pericardial effusion, a hyperechoic lesion with clear boundaries, a round, oval shape, lobulated with enormous size, vertical, right vertical, left atrium, and right atrium, aortic pressing lesion. The CT scan showed isohypodense lesions in the form of lobulated, partially indistinct boundaries, forced injection of contrast appeared inhomogeneous enhancement, the right lung had an increased bronchovascular pattern, and patches appeared on the dextra lung.Conclusion: The radiological imaging with x-ray, USG, and CT scan revealed that the patient found a mass in the mediastinum with firm boundaries, a round oval, homogeneous structure, fluid in the pericardial effusion, flat edges, and a homogeneous structure. Based on the findings, it can be concluded that radiological imaging can play a role in detecting germ mediastinum tumors.